2018
DOI: 10.1016/j.actbio.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of dense anisotropic collagen scaffolds using biaxial compression

Abstract: In vitro studies of cell-matrix interactions and the engineering of replacement materials for collagenous connective tissues require biocompatible scaffolds that replicate the high collagen density (15-25%/wt), aligned fibrillar organization, and anisotropic mechanical properties of native tissues. However, methods for creating scaffolds with these characteristics are currently lacking. We developed a new apparatus and method to create high density, aligned, and porous collagen scaffolds using a biaxial compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 66 publications
(69 reference statements)
1
47
0
Order By: Relevance
“…Scaffold-free approaches have also been used to generate zonal tissue and anisotropy; for example, anisotropic menisci with zonal variations have been produced using the self-assembling process 107 . These studies [104][105][106][107] suggest that recapitulating zonal and anisotropic properties of cartilage and menisci might be necessary to impart native functional properties to a tissue-engineered product.…”
Section: Self-assembling Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaffold-free approaches have also been used to generate zonal tissue and anisotropy; for example, anisotropic menisci with zonal variations have been produced using the self-assembling process 107 . These studies [104][105][106][107] suggest that recapitulating zonal and anisotropic properties of cartilage and menisci might be necessary to impart native functional properties to a tissue-engineered product.…”
Section: Self-assembling Processmentioning
confidence: 99%
“…Advances in scaffold-based and scaffold-free approaches have also focused on the recapitulation of native tissue architecture [104][105][106][107] . For example, stiffness gradient hydrogels (0.005-0.06 MPa) derived from poly(ethylene glycol) and chondroitin sulfate yield constructs with stiffness-dependent glycosaminoglycan gradients that mimic the glycosaminoglycan gradient found in articular cartilage between the superficial and deep zones 104 .…”
Section: Self-assembling Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to engineer tissues with higher concentrations of collagen, plastic compression of collagen gels has been investigated. In these systems, low density collagen gels are compressed, forcing water out and producing densified gels [34][35][36][37]. While these culture systems result in collagen densities similar to native tissue (100-250 mg/ml) and develop larger fiber-like morphologies, they lack the fibril level organization and do not replicate native tissue hierarchy [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…As it has long been identified that cellular physiology of disc cells is largely affected by the mechanical environment in AF tissues (Vergroesen et al, 2015), many engineered scaffolds have been fabricated for AF biomechanical restoration and pain relief, including natural scaffolds (Zitnay et al, 2018), synthetic polymers (Christiani, Baroncini, Stanzione, & Vernengo, 2019), and their combination (Yang et al, 2017). Among various types of scaffolds, in situ tissue-derived biomaterials, which closely mimic the prominent features of the native tissue microarchitecture and support an appropriate, tissue-specific cell phenotype, have their innate advantages in native tissue repair (Bejleri & Davis, 2019).…”
mentioning
confidence: 99%